Policy Communication on Twitter Social Media: Covid-19 Pandemic Control in Samarinda and Balikpapan City - Bambang Irawan; Achmad Nurmandi; Paisal Akbar (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2022)
Online media in disaster mitigation has received much attention from researchers. One of the most widely used online media is Twitter. Twitter is a type of social media that has become an effective medium for communication and socialization. The use of social media by the Government can make it easier for the Government to gather new ideas and opinions from the public, especially in this media. The social case related to Covid-19. This study aims to identify the communication of Covid-19 control policies at the City level, which is carried out through social media communication facilities. Samarinda City Government Twitter Account (@ppid_smr) and Balikpapan City Twitter account (@PemkotBPN). This study uses a qualitative method with a Qualitative Data Analysis (QDA) Miner approach used in the content, network, and cloud analysis using Nvivo 12 Plus software. The findings show that the intensity of each account has provided an overview of how the City Government is disseminating information related to the policies they produce. For the highest total tweet intensity and tweet intensity generated by the Samarinda City Government account @ppid_smr with a reasonably significant difference compared to the Balikpapan City Government account @PemkotBPN. In terms of analyzing the content of information shared related to the Covid-19 pandemic theme, each account has disseminated information directly related to the policy for handling and preventing Covid-19 cases in each city.Keywords: Policy communication, policy controlling, Covid-19, Samarinda, Balikpapan ABSTRAKMedia online dalam mitigasi bencana mendapat banyak perhatian dari para peneliti. Salah satu media online yang paling banyak digunakan adalah Twitter, Twitter merupakan salah satu jenis media sosial yang menjadi media komunikasi dan sosialisasi yang efektif. Penggunaan media sosial oleh pemerintah dapat memudahkan pemerintah untuk mengumpulkan ide-ide baru dan opini baru dari masyarakat, khususnya di media ini. Kasus sosial terkait Covid-19. Penelitian ini bertujuan untuk mengidentifikasi komunikasi kebijakan pengendalian Covid-19 di tingkat Kota yang dilakukan melalui sarana komunikasi media sosial. Akun Twitter Pemkot Samarinda (@ppid_smr) dan akun Twitter Pemkot Balikpapan (@PemkotBPN). Penelitian ini menggunakan metode kualitatif dengan pendekatan Qualitative Data Analysis (QDA) Miner yang digunakan dalam analisis konten, jaringan, dan cloud menggunakan software Nvivo 12 Plus. Temuan menunjukkan bahwa intensitas masing-masing akun telah memberikan gambaran bagaimana Pemerintah Kota menyebarluaskan informasi terkait kebijakan yang mereka hasilkan. Total intensitas tweet dan intensitas tweet tertinggi dihasilkan oleh akun Pemkot Samarinda @ppid_smr dengan perbedaan yang signifikan dibandingkan dengan akun Pemkot Balikpapan @PemkotBPN. Dalam hal menganalisis konten informasi yang dibagikan terkait tema pandemi Covid-19, masing-masing akun telah melakukan sosialisasi langsung terkait kebijakan penanganan dan pencegahan kasus Covid-19 di masing-masing kota.Kata Kunci: Komunikasi kebijakan, kebijakan pengendalian, Covid-19, Samarinda, Balikpapan